RELASIONAL BERPIKIR DENGAN BAHASA - Junifer Siregar (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2015)
This study wants to describe the relationship between the languages andmind in early childhood and want to describe the role of parents, teachers, andthe environment in developing language skills and thinking in early childhood.From the corner of the psychology of early childhood development is a child whohas limitations in the ability to think and speak. At this stage the child's way ofthinking, among others, still egocentric. Therefore that an increase in the child'sthinking, activities intended to enable them to perform classification, logicalthinking, and trained to solve problem.They should also be stimulated to learnabout a variety of concepts such as the concept of space, the concept of time, andthe concept of number. This research was conducted by using a qualitativedescription.Activities that can stimulate a child's ability to think is to improvechildren's language abilities. The language used by the teacher is a language thatraw organized yet simple and communicative. But in early childhood developmentto date is not known precisely the mechanism of how a child learns a language sothat the language can be learned.Based on the above, the authors are interested in doing research for "TheRelationship Between Thinking With Speak In Childhood".